COVID-19 pada Kehamilan: Apakah berbahaya? - Hanifa Salma Ramadhani; Nurul Islamy; Ade Yonata (Medula, 2020)
Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which spread rapidly throughout the world. These health emergencies, especially deadly in vulnerable populations and communities where health care providers are not adequately prepared to manage this infection. Pregnant women and fetuses represent high-risk populations in this pandemic. Study this article compiled using the literature review method, derived from journals and books resulting from literature searching from search engines (Google and Google Scholar) and electronic source of database (PubMed). There are 37 references reviewed in this article review. A challenge in treating pregnant patients affected by SARS-CoV-2. The explanation in the review of this article is to present a discussion of COVID-19 in pregnancy, intrauterine transmission, and fetal complications in the mother. Fetal health is something that must be taken into consideration during labor In addition, it needs to be focused on the safety of health workers in treating COVID-19 patients. COVID-19 in pregnancy is dangerous for mothers and infants, mothers with COVID-19 have clinical airway symptoms that will aggravate the state of pregnancy, for infants if intrauterine transmission occurs, COVID-19 in infants will cause ARDS (acute respiratory distress syndrome) so endangering lives. The clinical characteristics of pregnant women with COVID-19 are similar to non-pregnant adults. Fetal and neonatal outcomes appear to be good in some cases, but available data only cover pregnant women infected in the third trimester.